Blood Cell Profiles and Metamorphosis of Rice Field Frog (Fejervarya cancrivora) after Heavy Metal Copper (II) Sulfate Exposure - Haryanto, Haryanto; Fitri, Fadillya Maulidilla; Nurhayati, Sari; Fadilla, Aghniya Nur Rizka (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2024)
Tadpoles represent a critical stage in frog metamorphosis and are particularly susceptible to environmental stressors. Heavy metals, such as copper, are common industrial pollutants that adversely affect aquatic ecosystems. This study aimed to evaluate the effects of copper (II) sulfate on the blood cell profiles and metamorphic development of rice field frog (Fejervarya cancrivora) tadpoles. Experimental treatments included a positive control (mineral water), a negative control (Propylthiouracil / PTU 0.1 gL-1), and exposure to heavy metal of copper (II) sulfate 0.01 mgL-1 (Cu (II)). Each treatment group comprised nine tadpoles, maintained for 14 days under controlled conditions. After 14 days, the survival rate of tadpoles exposed to Cu (II) was 66.67%. Analysis of variance (ANOVA) revealed that Cu (II) exposure significantly impacted blood cell profiles (p < 0.05). Specifically, Cu (II) exposure led to reduced nuclear size, increased immature erythrocytes, and a higher percentage of abnormal erythrocytes. Although metamorphic growth parameters did not differ significantly among treatments (p > 0.05), Cu (II) exposure accelerated skin pigmentation and induced tail abnormalities, including tumor-like formations. These findings demonstrate that Cu (II) is toxic to the blood cells and induces morphological abnormalities in F. cancrivora tadpoles, highlighting the potential ecological risks of copper contamination in aquatic habitats.